SURG-15. SURVIVAL OUTCOMES FOLLOWING RE-RESECTION FOR RECURRENT GLIOBLASTOMA MULTIFORME. (11th November 2019) - Hennessy, Maeve; Dablouk, Mohamed; Mullally, William; O'Halloran, Philip; MacNally, Stephen; Morris, Patrick
Abstract: BACKGROUND: While the treatment of primary Glioblastoma Multiforme (GBM) is well defined, the role of surgical resection in recurrent GBM is not firmly established. 1 Treatment options for recurrent GBM include second-line chemotherapy, re-irradiation and surgical re-resection. 2 This review examines current practice in a national neuro-oncology centre. AIMS: To investigate survival outcomes in patients undergoing surgical re-resection for recurrent GBM in our institution and to compare our findings to the relevant published literature. METHODS: A retrospective review of our institution's neuro-oncology database was performed. We evaluated all patients who underwent re-resection for recurrent GBM following standard adjuvant treatment between 2015–2018. Patients who did not have an initial diagnosis of Grade 4 GBM and patients who were re-operated on within one month were excluded. We analysed overall survival using Kaplan Meier curves. Patients not known to have died were censored to the last known alive date. We also examined factors which may affect patient outcome, including age, sex, extent of resection, tumour characteristics and tumour location. RESULTS: 34 patients were eligible for inclusion into this study, of these 21 (61%) were male. Median age was 52. A radiologically confirmed initial resection of > 80% was achieved in 52% of patients. Median time from initial surgery to re-resection was 13.5 months. Median survival from initial surgery was 28.6 months and median survival after re-resection was 9.5 months. CONCLUSION: Re-operation appears to have a role in the management of recurrent GBM in carefully selected cases. Overall survival in this patient cohort remains poor and further studies into the benefit of re-resection in comparison to second-line chemotherapy and re-irradiation would be of value.